PREVALENCE, CHARACTERIZATION AND HETEROGENEITY STUDIES ON STREPTOCOCCUS MUTANS ISOLATED FROM BANGALORE URBAN POPULATION - DHAMODHAR P; SREENIVASA MURTHY; CHANNARAYAPPA; SHANTHAKUMAR SS; INDIRESHA H N (International Journal of Pharma and Bio Sciences, 2014)
Streptococcus mutans is a well-known causative agent in the development of dental caries. Over the last few decades there has been a remarkable increase in its prevalence rate among children and elders. In the present study, 38 % of S. mutans was isolated from the dental plaque samples collected from patients. Antibiotic sensitivity tests revealed the emergence of multi-drug resistance with all the isolates being completely resistant to penicillin, amoxicillin and ampicillin. Also, a decrease in sensitivity to Bacitracin was observed. The isolates were sensitive to the antibiotics erythromycin, clindamycin, ciprofloxacin and azithromycin. Further, Genomic DNA from all the clinical isolates and standard MTCC 497 was obtained and subjected further for PCR-RFLP analysis targeting the dex gene. RFLP with various restriction enzymes indicated that Hae III enzyme successfully digested the amplicons but the fragments had no heterogeneity among the resistant and the sensitive isolates including the standard.